Primary CNS vasculitis: insights into clinical, neuropathological, and neuroradiological characteristics - Sheikh, Tahani Saker; Rozenberg, Ayal; Merhav, Goni; Shifrin, Alla; Stein, Polina; Shelly, Shahar (Frontiers in Neurology, 2024)
Background and objectives Primary CNS vasculitis (PCNSV) is a rare inflammatory disorder that affects the blood vessels of the central nervous system (CNS). We aimed to analyze the neurological presentations, clinical follow-up, and long-term outcomes of patients with primary central nervous system vasculitis. Methods We conducted a retrospective analysis of medical records to assess the neurological presentation, rate of remission, and functional status at the last follow-up in patients with primary central nervous system vasculitis seen in our center in the last 13 years (2010–2023). Results We identified five patients, whose median age at symptom onset was 31 years (range: 15–41 years), including four male individuals (80%) from Muslim Arab (n = 4) and Ashkenazi Jewish (n = 1) backgrounds. Symptoms persisted for a median of 36 weeks (range: 3 weeks to 4 years) before diagnosis, with one case exceeding 3 years. Follow-up lasted a median of 56 months (range: 20–161 months). Clinical symptoms varied, presenting unilateral weaknesses (n = 2), cognitive and gait abnormality (n = 1), headaches (n = 1), and epileptic seizures (n = 1). MRI scans revealed abnormalities in the basal ganglia, corona radiata, parietal, and frontal lobes, showing hemorrhage, vasogenic edema, restricted diffusion, and enhancement post-gadolinium. All patients reported progressive holocephalic headaches and cognitive changes with overall progressive symptoms. Initial neurological examinations revealed abnormalities in all patients and included one or more of the following: cognitive or visual impairment (n = 2), seizures (n = 1), and unilateral UMN signs (n = 2) at the initial neurological examination, all but one patient required walking aids including (cane 2, wheelchair, bedridden 1). Patients were stable (n = 2), deteriorated (n = 1), or improved (n = 2). Following treatment, two patients still required ambulatory aids, with one using a cane and the other using a wheelchair, while the remaining three did not require any ambulatory aids. Discussion The study on PCNSV highlights varied symptoms and diagnostic challenges, including delayed diagnosis and a spectrum of neurological issues from cognitive impairments to seizures. Brain biopsies showed lymphocytic infiltration, thrombi, and necrosis. Immunotherapy significantly improved clinical and radiological outcomes. Over 56 months of follow-up, outcomes varied from stability and deterioration to improvement.